INSTITUTIONAL GOUVERNANCE IN THE DEVELOPMENT OF DISASTER RESILIENT TOURISM VILLAGES (CASE STUDY: SIMANGULAMPE VILLAGE, BAKTIRAJA DISTRICT, NORTH SUMATERA) - Sartika Purba, Dewi
Simangulampe Tourism Village in Baktiraja Subdistrict has become one of the tourist destinations located precisely in the Lake Toba area, surrounded by hilly terrain. The location of this tourism village is vulnerable to natural disaters such as landslides and floods, which typically not only damage the environment but also result in loss of life. To prevent the occurrence of such disasters, mitigation efforts must be undertaken by various actors involved in the governance of the Simangulampe Tourism Village in Baktiraja Subdistrict. The objective of this study is to understand institutional governance in the development of a disaster-resilient tourism village in Simangulampe, Baktiraja Subdistrict. The research was conducted in August 2024, with primary data collected through field observations and interviews with involved actors. Secondary data collection involved information on disaster mitigation in Simangulampe Village obtained through literature reviews on previous research. This research results indicate that Simangulampe Tourism Village falls into the category of a Pratama Resilient Village with a calculated score of 55,50.